Bimbingan Belajar Vocabulary MI & SD Di Desa Nglaban Jombang - Khudriyah Khudriyah (An Naf'ah: Jurnal Pengabdian Masyarakat, 2023)
Vocabulary is important in communication the students who are capable in mastering vocabulary will be easy to understand English text. they will easily understand the contents of the text. However, many students do not master it, including students who live in Nglaban. This guidance aims to help those students, and the results of the guidance can be concluded that the assistance in learning English for class II MI/SD students in Nglaban using drill method, and game techniques and picture is very effective and has a positive impact, the students vocabulary seems increased significantly, because it can be seen from the comparison of pretest and posttest values with the paired sample test that the results are t count > t table (6, 689 > 2, 16037, this means the learning is successful.